Global e-government theory, applications and benchmarking - Al-Hakim, Latif 1946- (Information quality management series, 2007)
This handbook provides helpful examples from practitioners and managers involving real-life applications, while academics and researchers in the fields of information systems and e-government contribute theoretical insights.